Debates in transgender, queer, and feminist theory: contested sites - Elliot, Patricia (Ashgate, 2010)
Intersecting the domains of women's studies, sexuality, gender and transgender studies, Debates in Transgender, Queer, and Feminist Theory provides a critical analysis of key texts and theories, engaging in a dialogue with prominent theorists of transgendered identity, embodiment and sexual politics, and intervening in various aspects of a conceptually and politically difficult terrain.
Keywords: LGBTQIA2+; approches et analyses; corps; cours; discipline; identités LGBTQIA2+; lit4700; premier cycle; ressource en ligne; sciences humaines; sociologie; thématiques; transféminisme